MACROECONOMETRIC STABILIZATION AND IMF POLICIES: A SURVEILLANCE OF INFLATION - Christopher E.S. WARBURTON (Revista Galega de Economía, 2015)
This paper uses time series data from 1960 to 2012 to evaluate the long-run relationship between aggregate money supply and changes in the general price level (inflation) for a selected group of countries with historically stable prices and episodes of very high inflation. Recent paradigmatic shifts from exchange-rate-based stabilization policies to conditionalities involving price stability have greatly influenced the empirical work of this paper. Empirical results indicate that the money supply and inflation are cointegrated in some countries with high spells of inflation, such as Argentina, Brazil, and Mexico, but that the variables may not be cointegrated with each other for countries with prices that are generally and historically stable, such as the UK and the US. The paper highlights the need for good quality governance, employment, and productivity in surveillance measures that are designed to obtain external balance.